Akselerasi Pemahaman Al-Qur’an Hadits Siswa MAN 2 Bukittinggi Melalui Model Pembelajaran Kolaboratif - Reki Alfarizky Ramadhan; Salsabila Asura; Rugaiyah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to examine the effectiveness of implementing collaborative learning methods in improving students’ understanding of the Al-Qur’an Hadith subject at MAN 2 Bukittinggi. The study is motivated by the low level of student engagement in conventional, teacher-centered learning, which limits active student participation. In line with the implementation of the Kurikulum Merdeka, which emphasizes collaboration, meaningful learning, and project-based activities, a more interactive and contextual learning approach is required. This research employs a qualitative approach with a descriptive design. Data were collected through in-depth interviews with three Al-Qur’an Hadith teachers who had implemented collaborative learning for at least one semester, supported by classroom observations and analysis of lesson plan documents. Data analysis followed the Miles and Huberman model, including data reduction, data display, and verification through source triangulation. The study was conducted from May to June 2025. The findings indicate that collaborative learning is effective in increasing student engagement, improving understanding of Qur’anic verses, and enhancing contextual interpretation analysis skills. In addition, this method fosters socio-religious values such as cooperation, responsibility, and tolerance for differing opinions, making it relevant for Al-Qur’an Hadith learning in the digital era.